(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Rheumatoid arthritis is a serious dribbling autoimmune disease that damage joints in symmetrical pattern and if not controlled timely then may lead irreversible disability and then may also damage to the internal organs. Rheumatoid arthritis leads joint pain, stiffness and swelling fatigue and different mental problems such as anxiety, irritation, depression and sleep deprivation. Objective: The study aimed to assess the effect of hand reflexology massage on pain, fatigue and sleep deprivation in patients suffering from rheumatoid arthritis. Methods: The study on 20 RA patients at Liberty Hospital in Jaipur used a quasi-experimental research design from March 3, 2022 to March 28, 2022. The participants were selected by a simple random sampling technique and randomly divided into experimental (n = 10) and control (n = 10) groups. Patients in the experimental group participated in hand reflexology massage, while patients in the control group received only routine care The study tools included the Numeric Rating Scale (NRS), the Fatigue Assessment Scale (FAS), and the Pittsburgh Sleep Quality Index (PSQI). Data were analyzed by SPSS 22.0 software using Fisher’s exact test, chi-square test, and paired t-test. Results: The study result findings revealed that there was significant reduction in joint pain, fatigue and sleep deprivation after administration of hand reflexology( p=0.005) Conclusion: Hand reflexology can be considered an effective intervention in reducing level of pain, fatigue and sleep deprivation among rheumatoid arthritis.